IT GOVERNANCE AUDIT AT THE KAMPAR REGENCY LIBRARY AND ARCHIVES DEPARTMENT USING COBIT 2019 AND ITIL 4 - Bayu Putra; Muhammad Jazman; Megawati Megawati; Febi Nur Salisah (Jurnal Teknik Informatika (Jutif), 2022)
Information Technology (IT) is a tool that plays an important role in helping improve the effectiveness and efficiency of a company's or organization's business processes. The Kampar Regency Library and Archives Service uses the Integrated Library System (INLIS) Lite to support operational, management, and decision-making functions in the library. However, the use of INLIS Lite has not been fully utilized properly, for this reason it is necessary to carry out an IT governance audit. The audit process aims to determine the extent of IT performance, human resources, and the level of IT maturity in the library. This study uses Control Objective for Information and Related Technology (COBIT) 2019 and Information Technology Infrastructure Library (ITIL) 4 to conduct audits. With the findings of the audit results obtained eight process domains, namely APO02 and APO012 domains are at level 1 (Performed) in the Largely Achieved category, APO09 and BAI08 domains are at level 2 (Managed) in the Largely Achieved category, domains APO013, BAI05 and MEA01 are in the Largely Achieved, and the APO07 domain is at level 4 (Predictable) and in the Fully Achieved category. In addition to the audit, an assessment of the capability level was also carried out using the Servqual Model and Importance Performance Analysis with the results of obtaining 2 criteria in quadrant A, 1 criterion in quadrant B, 2 criteria in quadrant C and 3 criteria in quadrant D. This study also provides recommendations for improvement using SWOT model approach refers to ITIL 4.